Embodied Revelation: A Classic Grounded Theory of Heart Failure Patient Decision Making Surrounding Primary Prevention Implantable Cardioverter Defibrillator Therapy - Vera Barton-Caro Ph.D., (Grounded Theory Review: An International Journal, 2015)
The purpose of this classic grounded theory study was to explain the complex decision making process of heart failure (HF) patients considering primary prevention implantable cardioverter defibrillator (ICD) therapy. Sudden cardiac death (SCD) is the leading cause of death for people with HF as well as the primary cause of death in the United States (US). ICDs represent the standard of care as the only effective therapy for primary prevention of SCD. However, a significant proportion of qualifying HF patients declines this invasive, yet life-saving device. The grounded theory is of Embodied revelation. The threat of SCD for ICD candidates consists of four stages: living in conscious denial, heightening of awareness, sanctioning ICD therapy, and living in new assurance. The first stage ends abruptly with the critical juncture of grasping the threat of SCD. This grounded theory has implications for research, nursing and medical practice, as well as bioethical considerations.